(untitled) (Journal of Engineering, 2015)
Recycled asphalt concrete mixture are prepared, artificially aged and processed in the laboratory to maintain the homogeneity of recycled asphalt concrete mixture gradation, and bitumen content. The loose asphalt concrete mix was subjected to cycle of accelerated aging, (short –term aging) and the compacted mix was subjected to (long -term aging) as per Super-pave procedure. Twenty four Specimens were constructed at optimum asphalt content according to Marshall Method. Recycled mixture was prepared from aged asphalt concrete using recycling agent (soft asphalt cement blended with silica fumes) by (1.5%) weight of mixture as recycling agent content. The effect of recycling agent on aging after recycling process behavior of asphalt concrete was determine. Aged specimens after recycling process were prepared by subjecting the recycled asphalt concrete to accelerated aging and tested for resistance to moisture damage. The improvement in the resistance to moisture damage of aged mixture after recycling with (soft asphalt cement blended with silica fumes) was 76.17% as compared to the corresponding aged mixture before recycling process. The ITS for unconditioned specimens for aged after recycling process mixture was less than reference by 67.1%, and less than that of aged before recycling process mixtures by 64.1%.